2013
DOI: 10.1111/jace.12711
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent Mg0.27Al2.58O3.73N0.27 Ceramic Prepared by Pressureless Sintering

Abstract: A novel aluminum magnesium oxynitride transparent ceramic with the chemical formula Mg0.27Al2.58O3.73N0.27 was firstly prepared by pressureless sintering of fine single‐phase powders at 1875°C for 24 h in nitrogen atmosphere. The ceramic was fully dense with the average grain size of 57.5 μm. The sample showed excellent in‐line transmission from the visible to middle‐infrared wavelengths with the maximum transmittance of 84%, which could be attributed to rare pores in the sintering body. The material also exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Polycrystalline Mg 1– x Al 2(1+ x /3) O 4 samples were prepared by a conventional solid-state method, which has been employed to synthesize spinel-type MgO·1.5Al 2 O 3 , AlON, and MgAlON in our previous studies. Commercial MgO (∼99.9%) and α-Al 2 O 3 (∼99.99%) powders were used to synthesize Mg 1– x Al 2(1+ x /3) O 4 with designed compositions of x = 0, 0.12, 0.25, 0.53, 0.6. The XRD patterns were recorded on a PANalytical X’Pert Pro X-ray diffractometer equipped with monochromated Cu Kα radiation (1.540598 Å, 40 kV, 40 mA).…”
Section: Experimental Detailsmentioning
confidence: 99%
“…Polycrystalline Mg 1– x Al 2(1+ x /3) O 4 samples were prepared by a conventional solid-state method, which has been employed to synthesize spinel-type MgO·1.5Al 2 O 3 , AlON, and MgAlON in our previous studies. Commercial MgO (∼99.9%) and α-Al 2 O 3 (∼99.99%) powders were used to synthesize Mg 1– x Al 2(1+ x /3) O 4 with designed compositions of x = 0, 0.12, 0.25, 0.53, 0.6. The XRD patterns were recorded on a PANalytical X’Pert Pro X-ray diffractometer equipped with monochromated Cu Kα radiation (1.540598 Å, 40 kV, 40 mA).…”
Section: Experimental Detailsmentioning
confidence: 99%
“…Moreover, yttria possesses a broader range of transparency, a lower high-temperature infrared (IR) emissivity, and a higher theoretical thermal conductivity compared to the aforementioned conventional transparent ceramics, which make transparent yttria ceramics better TA B L E 1 Physical properties of transparent Y 2 O 3 , YAG, AlON, and MgAl 2 O 4 ceramic materials. [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Researchers have conducted a large number of theoretical and experimental studies on the phase diagram, crystal structure, preparation, and properties of transparent ceramics of MgAlON. [10][11][12] It has been found that the infrared optical transmittance of the MgAlON transparent ceramics is better than that of the AlON transparent ceramics, but the mechanical properties of the former are difficult to surpass those of the latter. Clay et al developed a series of research studies on the synthesis and preparation of LiAlON transparent ceramics using LiAl 5 O 8 , Al 2 O 3 , and AlN as raw materials.…”
Section: Introductionmentioning
confidence: 99%